2017
DOI: 10.1111/tri.12897
|View full text |Cite
|
Sign up to set email alerts
|

Former smoking and early and long-term graft outcome in renal transplant recipients: a retrospective cohort study

Abstract: Smoking is associated with unfavourable outcome in solid-organ transplant recipients. Nicotine may predispose to kidney injury by increasing oxidative stress. We hypothesized that former smoking negatively affects graft outcome in kidney transplant recipients and especially those with delayed graft function (DGF). We included adult recipients of a kidney transplant between 1 January 2003 and 1 October 2015 at Ghent University Hospital and recorded outcomes until 31 October 2015. We used Kaplan-Meier and multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Bad habits, in particular, smoking, have a definite adverse effect on graft adaptation. In particular, a study by Van Laecke et al 43 proved that recipients who smoked for a long time before surgery had a 10-year risk of rejection 65% higher than patients who never smoked. And in those who did not quit smoking after the transplant, the rejection rate was as high as 98%.…”
Section: Resultsmentioning
confidence: 99%
“…Bad habits, in particular, smoking, have a definite adverse effect on graft adaptation. In particular, a study by Van Laecke et al 43 proved that recipients who smoked for a long time before surgery had a 10-year risk of rejection 65% higher than patients who never smoked. And in those who did not quit smoking after the transplant, the rejection rate was as high as 98%.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Van Laecke et al . [ 31 ] reported in a single centre retrospective study including 1013 KT recipients (KTRs) an incidence of active smokers after transplantation of 7%. Also, a study including 4110 KTRs revealed an incidence of current smokers of 11% [ 32 ].…”
Section: Epidemiology Of Smoking Kt Candidates/recipientsmentioning
confidence: 99%
“…Interestingly, quitting cigarette smoking for >5 years before KT was associated with a 34% relative risk reduction for graft failure [ 34 ]. In addition, although former smokers have increased long-term graft and death-censored graft loss rates compared with never smokers, this association is much stronger in patients who restarted or continued smoking after KT [ 31 ].…”
Section: Impact Of Tobacco Use On Ktr Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking by kidney transplant recipients has been significantly associated with impaired graft and patient survival and increased cardiovascular events [9–15]. Relatively few studies have demonstrated that the smoking status of donors is a significant risk factor for decreased graft and recipient survival, as well as decreased post‐transplant kidney function [13,16,17].…”
Section: Introductionmentioning
confidence: 99%